Interactive commodity loop - Gvozden, Vladimir (Array, 2019)
The commodity is recognized as an essential element of our world. If our relationship with commodity as the structuring form of capitalist society is an ongoing process of subjective work and the exchange of meanings, then the question of historical ontology becomes inevitable. Historical ontology means that “we constitute ourselves at a place and time, using materials that have a distinctive and historically formed organization” (I. Hacking). This paper is an attempt to interpret commodity through the extension of two concepts developed by Ian Hacking (the looping effect, the making up people), and their connection with the philosophical approach to economy. The looping effects of commodity create a special ambience, special forms of connection and separation, equality and hierarchy, community and singularity, freedom and affirmation. The article gives a short historical account of the emergence of the commodity loop (from the 1850s to 2001), and singles out the importance of the structural determinations of capitalism (the ideology of free market, property, state mechanisms, a specific type of culture, etc.). The “making up people” inside the commodity loop presumes the people who count, take part in the marketising, imagine the market in every situation, interiorize the market-conforming sense of guilt and responsibility, and, paradoxically, will be ready to be self-entrepreneurs, to participate in own making up. It is shown that contemporary doxa becomes evident from the perspective of the commodity loop, although it creates a context of harmony and reduces complexity. As the analysis goes deeper, we are discovering interactive nodes at steadily increasing levels of intensity but also two possible productive points of resistance (inequality, immigration). The commodity loop is an ontological fabric in which all threads are woven together, from political and economic to social and personal relationships.